2016
DOI: 10.1007/978-3-319-52804-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of cultural heritage Materials: Overview of Applications and New Frontiers in Instrumentation, Sampling Modalities, and Data Processing

Abstract: Abstract:Rooted in the long tradition of Raman spectroscopy of cultural heritage materials, in this work we provide a personal perspective on recent applications and new frontiers in sampling modalities, data processing, and instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 134 publications
0
9
0
Order By: Relevance
“…Raman spectroscopy can thus provide crucial information about the chemical structure of organic materials, but requires robust and optimized analytical strategies and/or data processing. Several methods have been developed to remove, a posteriori , the undesired contribution of luminescence and ripples in Raman spectra [33,35] . Note that in the papers discussed here [15-20] , such processing would leave no signal other than the mineral peaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman spectroscopy can thus provide crucial information about the chemical structure of organic materials, but requires robust and optimized analytical strategies and/or data processing. Several methods have been developed to remove, a posteriori , the undesired contribution of luminescence and ripples in Raman spectra [33,35] . Note that in the papers discussed here [15-20] , such processing would leave no signal other than the mineral peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when a sample is illuminated by the laser, the presence of structural defects and inorganic/organic components can generate significant luminescence, often overwhelming the weak Raman signal [21,27] . When this background luminescence is intense, the transmission properties of the interferometric edge filter used to reject the Rayleigh line induce quasi-periodic “ripples” in the measured spectrum [33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used for in situ analysis to determine organic and inorganic substances on a stone substratum including conservation chemicals such as consolidants and water repellents. A Raman spectrometer is very useful when there is no documented report on previous conservation treatment [40,41], which is attributable to its ability to identify conservation treatments. Results obtained by Dominguez-Vidal and de la Torre-Lopez [42] on in situ characterization of plasterwork decorations of the Hall of the Kings in the Alhambra (Granada, Spain) with a Raman microspectrometer showed that they consist of different types of pigments.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…The analysis of natural organic dyes and pigments in cultural heritage objects is challenging in many aspects, including low concentration, susceptible to degradation and presence in complex matrices, which requires highly sensitive analytical tools. While the non-invasive quality of spectroscopic techniques is not to be underestimated, [77,78] the information gained is often distorted, as the organic colorants are frequently found in complexed form with metal ions, either bound to cloth fibers or embedded in paint layers in the form of lake pigments. Chromatographic separation, in contrast, despite requiring sampling, can address this level of complexity, where individuals are separated from their matrix and different components present in a dye mixture may be discriminated.…”
Section: Dye Analysis and Theoretical Basis For Csramentioning
confidence: 99%